Public Perceptions of African Diaspora Religions in the United States - Danielle N. Boaz (Religions)
This article investigates public perceptions of African diaspora religions, especially Santeria and Vodou, in the United States. Relying on three public opinion surveys carried out in 2023 and 2024, it explores broad views of these religions as well as levels of knowledge and sources of information about them. Most significantly, this article interrogates whether public opinion surveys support scholars’ frequent assertions that African diaspora religions are misunderstood and maligned, plagued by discriminatory public perceptions.